Implementasi Manajemen Keuangan di Madrasah Tsanawiyah Muhammadiyah - Suparman, Suparman (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2024)
One aspect that is very important to produce superior students is the financial aspect. The financial management of an educational institution/school is very important in implementing the activities of an educational institution/school. There are various sources of funds managed by schools, both from the government in the form of BOS funds and from funds from the community in the form of tuition fees. The purpose of this study was to analyze the existing forms of financial management at MTs Muhammadiyah 02. The method used in this study was qualitative through literature and field studies. The stages of the research were carried out by collecting library sources, both primary and secondary. Phase two, this research was also carried out through field studies. Initially, the research design and field testing tools were prepared. The next stage was carried out at the research location, respondents and informants. In conducting field research, observations, documentation and interviews were carried out. The education financial management system can be seen by the implementation of financial management functions in financial management in this Madrasah which starts with planning, implementing, supervising and accountability of Madrasah finances which are going well in accordance with the principles of education financial management. Fund management that has been carried out in this Madrasah is (1) planning which includes: preparation of RKAM and RAB BOS, (2) implementation which includes: channeling and allocating funds, using BOS funds, spending funds in Madrasahs, bookkeeping and taxation related to fund management, (3) Monitoring and evaluation which includes: implementation of supervision by internal and external parties and evaluation by Madrasah heads and Madrasah committees, (4) Reporting which includes: reporting of the use of funds and publication of the use of funds